An Optimization-Based Method for the Explicit Production Data Analysis of Gas Wells - Zhang, Lixia; Li, Yong; Song, Xinmin; Wang, Mingxian; Yu, Yang; He, Yingxu; Zhao, Zeqi; Liu, Chenchao (Frontiers in Energy Research, 2022)
This work aims at the exploration of production data analysis (PDA) methods without iterations to overcome the limitations of advanced type curve analysis relying on the iterative calculation of material-balance pseudotime and the shortcomings of current explicit methods reckoning on specific production schedule assumptions. The dynamic material balance equation (DMBE) is strictly proved by the integral variable substitution based on the gas flow equation under the boundary dominated flow (BDF) condition and the static material balance equation (SMBE) of a gas reservoir. Then we introduce the pseudopressure level function (p) and the recovery factor function R(p) to rewrite the DMBE in terms of observed variable Y and estimated variable Ye which can transform the PDA into an optimization problem of minimizing the error between Y and Ye. An optimization-based method for the explicit production data analysis of gas wells (OBM-EPDA), therefore, is developed in the paper, capable of determining the BDF constant and gas reserves explicitly and accurately for variable rate and/or variable flowing pressure systems. Three stimulated cases demonstrate its applicability and validity with small errors less than 1% for estimated values of reserves and Y. The field case analysis further proves the practicability of OBM-EPDA, and the analysis results compare favorably with previous studies. It is shown that the nonlinear relation of  to R can be represented by a polynomial function merely dependent on the inherent properties of the gas production system even before sorting out the production data. The errors of observed variable Y provided by OBM-EPDA facilitate the data quality control, and the elimination of outliers not subject to the BDF condition improves the reliability of the analysis. For various gas systems producing whether at a constant rate, a constant bottomhole pressure (BHP), or under variable rate and variable BHP conditions, the proposed method gives insights into the well-controlled volume and production capacity of the gas well whether in a low-pressure or high-pressure gas reservoir, where the compressibilities of rock and bound water are considered.